Sacrament and Sacrifice: Attending to Some Neglected Biblical Threads - Watts, A. M. (Toronto journal of theology, 2008)
Whereas we can connect with the story of the giving of the Commandments, it is very difficult for us to do so with this incident. It reflects the age when the places of worship were noisy and bloody and smelly. The bawling of animals and the cooing of turtledoves were an integral part of life around an altar. When contemporary Christians hear or read the "cleansing of the temple" scene in the gospels, we tend to see it as an effort by Jesus to clean the Temple up and get rid not only of the commercialism but also of all the ugly sacrificial elements. That is an interpretation not justified by the text. When Jesus quoted the words about the Temple being a house of prayer for all nations, he was not referring to quiet prayer murmured in a quiet place. It is true that when Jesus began to throw things around in the Temple that day, he drove out the animals along with the money changers. But he was not trying to get rid of the noise and the smell in order to secure the hushed, hygienic conditions we now require in our churches. He was trying to get rid of the profiteering that had developed around the money changing. And if people like N.T. Wright are correct in saying that Jesus was in part signalling the end of the Temple, it was not on the ground that sacrifice had always been a pointless exercise but that the significance of what had been taking place in the temple was now to be gathered up in Christ..